Post-Covid-19 Gender Inequality in Global Employment: A Difference-In-Difference Analysis - Lei, Weng Chi (Atlantis Press, 2024)
The fifth Sustainable Development Goal of the United Nations targets achieving gender equality by 2030, but recent progress has been sluggish. Gender inequalities in the labor markets may have been exacerbated by the Covid-19 recession. This paper aims to investigate the effects of the Covid-19 pandemic on gender inequalities in the labor markets by...